Waking up on another September 12th: implications for intelligence reform. Issue 5 (28th July 2016) - Travers, Russell E.
Abstract: After 9/11 the US Government tried to 'fix' intelligence by adopting the Intelligence Reform and Terrorism Prevention Act (IRTPA). Resources increased and, to varying degrees, performance improved – particularly in counterterrorism. This article, however, argues that the constellation of Intelligence Community authorities and organizations, either created or left in place by the IRTPA, coupled with the challenges of a complex security environment, leaves us ill-prepared to deal with the Country's twenty-first century intelligence requirements. Should that critique prove accurate, and should future intelligence failure(s) be judged strategically and politically unacceptable, the second half of the article provides a framework for revising the IRTPA; the proposals substantially increase the authority of the head of the Intelligence Community, consolidate structures, and create centers of analytic critical mass necessary to meet the knowledge requirements for both regional and transnational security issues. Reflecting the Intelligence Community's long standing tradition of questioning assumptions, the article is meant to foster reflection and debate about whether the Intelligence Community is postured to meet the needs of the Country, and if not, what needs to change.